Fig trees (Ficus carica L.) leaf nutrients contents with potassium fertilization - Oliveira Brizola, Rubem Marcos de; Leonel, Sarita [UNESP]; Tecchio, Marco Antonio [UNESP]; Hora, Rerison Catarino da [UNESP] (Univ Federal Lavras-ufla, 2005)
Potassium rates were evaluated in fig trees cv Purple of Valinhos during first development years. The experimental design was in randomized blocks with four replications and six treatments. The plots were splited in the evaluations months. The treatments were six potassium fertilization rates (0, 30, 60, 90, 120 and 150 g per plant of K2O). The potassium fertilization was made in covering. The nutrients contents of fig trees were evaluated five months after the winter pruning, through the leafs and petioles samples. In the second year, the nutrients contents showed to be competition between potassium and magnesium in the rates higher than 50 g of K2O per plant. The nitrogen and sulfur contents were not modified by the increases in the potassium rates. The phosphorus rates had linear increases.
Keywords: Ficus carica L.; leaf nutrientes status; potassium